2024
DOI: 10.1136/jitc-2023-008450
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic monitoring of circulating tumor DNA reveals outcomes and genomic alterations in patients with relapsed or refractory large B-cell lymphoma undergoing CAR T-cell therapy

Hesong Zou,
Wei Liu,
Xiaojuan Wang
et al.

Abstract: BackgroundOver 50% of patients with relapsed or refractory large B-cell lymphoma (r/r LBCL) receiving CD19-targeted chimeric antigen receptor (CAR19) T-cell therapy fail to achieve durable remission. Early identification of relapse or progression remains a significant challenge. In this study, we prospectively investigate the prognostic value of dynamic circulating tumor DNA (ctDNA) and track genetic evolution non-invasively, for the first time in an Asian population of r/r patients undergoing CAR19 T-cell the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…ctDNA < 10 LG/mL or between 10 and 100 LG/mL had similar 1-year PFS of 78% and 77% and similar 1-year OS of 90% and 91%, respectively, whereas concentrations between 100 and 1000 and >1000 LG/mL both had median PFS of 3 months, while median OS was 19 months and 7.4 months, respectively [67]. Lastly, Zou et al reported that low pre-LD ctDNA (n = 11) predicted superior 1-year PFS (81.8 vs. 33.3%, p = 0.031) and OS (90 vs. 46.7%; p = 0.023) [68].…”
Section: Pre-car-t Therapy Risk Stratificationmentioning
confidence: 99%
See 3 more Smart Citations
“…ctDNA < 10 LG/mL or between 10 and 100 LG/mL had similar 1-year PFS of 78% and 77% and similar 1-year OS of 90% and 91%, respectively, whereas concentrations between 100 and 1000 and >1000 LG/mL both had median PFS of 3 months, while median OS was 19 months and 7.4 months, respectively [67]. Lastly, Zou et al reported that low pre-LD ctDNA (n = 11) predicted superior 1-year PFS (81.8 vs. 33.3%, p = 0.031) and OS (90 vs. 46.7%; p = 0.023) [68].…”
Section: Pre-car-t Therapy Risk Stratificationmentioning
confidence: 99%
“…Zou et al identified baseline mutations associated with higher risk of disease progression after CAR-T therapy and resultant inferior PFS and OS including IGLL5, CD79B, P2RY8, ETV6, and KLH6. Interestingly, co-occurrence of TP53 and IGLL5 mutations was observed more frequently in patients with disease progression, suggesting a synergistic role in tumorigenesis and resistance to CAR-T therapy [68]. Lastly, Zhou et al reported mutations at the time of initial diagnosis in GNA13, SOCS1, TNFAIP3, and XPO1 were associated with R/R disease after CAR-T therapy [75].…”
Section: Prognostic Role Of Tumor Mutational Burden and Evaluation Of...mentioning
confidence: 99%
See 2 more Smart Citations